Pengkulturan Sampel Susu Fermentasi yang Mengandung Probiotik dan Identilikasinya dengan PCR - AMARILA MALIK; INDRIANI INDRIANI; LILIANA SARAGIH; MAKSUM RADJI (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Lactic Acid Bacteria (LAB) has long been used in fermented milk because its stability, unique taste and texture and also for its health benents that are provided by the probiotic. There are many fermented dairy products in the market nowadays that declared containing living culture or as probiotics. The aim of this study was to identify LAB from fermented milk product by Visual inspection on plate culture for their morphology, as well by molecular technique performing PCR and DNA sequencing methods. Morphology and growth incubation time of each isolate was observed. A pair of primer that is highly speciiic for LAB targeting the gene encoding for 168 rRNA, which represents sequences of region 677 to 693 of E. coli numbering has been used for PCR identiiication in this study. A total of nineteen isolates were obtained from 10 fermented milk samples that were grown on de Mann Rogosa Sharpe Agar (MRSA) media. Nine out of 19 isolates which represent each of the samples were selected. Genomic DNA extracted from those 9 isolates were used as template for PCR. The results showed that 8 amplicons were positively identitied as LAB, but only three identities indicated similar species as declared, while 5 others did not.